4 - Trente ans de critique du système soviétique (1960-1990) - Amin, Samir (Africa Development, 1991)
Abstract : With the exception ofthose individuals with a natural disposition to make predictions , nobody can boast not being somewhat taken aback by the rapid and total collapse of the political and economic systems in Eastern Europe and in the Soviet Union. Yet, after the surprise effect has passed , it is good to return to the analyses of such systems one and all have produced over the past thirty years. Even if I may sound pretentious. I dare say that I have situated myself since I960 in a leftwing mainstream - a very minority one - which had foreseen roughly what ultimatelybrutally took place between 1989 and 19911. Of course, such a collapse we considered as highly likely , was not the only possible outcome to the crisis in the Soviet system. I do not believe in any unfailing linear determinism in history. The possibility of the Soviet regime falling toward the right (what has actually happened) or toward the left , has always been present. The latter possibility , which is now ruled out for the immediate future , is still on the agenda of history, not only because there is never an end to history, but also and mainly because I seriously doubt that the leftwing solution at work will stabilize the Eastern societies, even in the mid-term. Hence, the struggle for an alternative solution to their problèmes continues.